2013
DOI: 10.5402/2013/206539
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model and Experimental Evaluation of Drag Torque in Disengaged Wet Clutches

Abstract: When the clutch is in disengaged condition, ideally no torque should be transmitted. However, in reality, the relative motion between the disks causes viscous shearing of fluids in the gap. This results in a drag torque which is considered as a loss. The objective of the present study is to formulate a drag torque model as well as to experimentally evaluate the effect of several parameters on the drag torque. A model based on continuity and Navier-Stokes equations, considering laminar flow, is deduced. The dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…9 Comparison of model and test result rpm which aligns well with the test data despite significant difference in the torque magnitude. On the contrary, the speed corresponding to peak torque from the model predictions of Yuan et al [8] and Iqbal et al [9] is around 400 rpm and that in case of Kato et al is 370 rpm. Clearly, the DT curve predicted by the proposed model is closer to the test data compared to the other models both in terms of the torque magnitude and peak occurrence.…”
Section: Comparision With Different Models and Test Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…9 Comparison of model and test result rpm which aligns well with the test data despite significant difference in the torque magnitude. On the contrary, the speed corresponding to peak torque from the model predictions of Yuan et al [8] and Iqbal et al [9] is around 400 rpm and that in case of Kato et al is 370 rpm. Clearly, the DT curve predicted by the proposed model is closer to the test data compared to the other models both in terms of the torque magnitude and peak occurrence.…”
Section: Comparision With Different Models and Test Resultsmentioning
confidence: 86%
“…In 2013, Iqbal et al [9] presented a Drag Torque (DT) model accounting the effect of cavitation in laminar flow.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the necessity of better-understanding the physics of the fluid mechanics problem as well as the need for the extraction of fast generic results, has led many researchers into putting efforts in deriving analytical solutions of the similar-type flow problems [7][8][9]. Those efforts are concentrated in deriving truncated forms of the Navier Stokes equations set that are analytically solvable.…”
Section: Analytical Modelingmentioning
confidence: 99%
“…Ratio δ versus radial clearance, design point 3. r z Observing the Figs. (7)to(8) it is concluded that the dependence of δ on ḣ and ω 1 is negligible and therefore ̇ .…”
mentioning
confidence: 97%
“…Therefore, the gap between the piston and clutch plates for the oncoming clutch should be eliminated when the clutch torque capacity is near zero at the end of the clutch fill phase [6,7]. Nowadays most clutch torque models do not take hydraulic dynamic characteristics into account [8]. To optimize the engagement of clutches, clutch fill is usually formulated as an optimization problem.…”
Section: Introductionmentioning
confidence: 99%